Pembatalan dan penggantian tanah rizab melayu negeri Perlis: Analisis kritikal - Raziff, Yaacob (2021)
The issue of replacement failure of Malay Reserve Land (MRL) revocation continues to be debated as it is becoming an important economic factor in the socio-economic development of the Malay community. Therefore, the challenges of the implementation and enforcement of the Malay Reserve Enactment (MRE) should be reviewed. Hence, this study aims to discuss the administrative and legal structure of MRL in Perlis as well as to examine the method of revocation practice and replacement of MRL based on the provisions under Federal Constitution. The causes and effects of MRL replacement failure are also reviewed to ensure the continuity of MRL. Qualitative method has been used in this study to obtain a more detailed information on the location of the study which is the Perlis State. Data collection was made through semi-structured interviews with eight informants that include experts (constitution, legislation, planning, development), Non-Governmental Organizations (housing, politics), implementers (land affairs), and industry (developer). The secondary sources of research on official and unofficial documents are also used. The findings show that the administrative structure of MRL comprise of the King, Legislative Assembly, Executive Council and Land and Mines Office. Meanwhile, regulatory methods, enforcement, exceptions, and resolution of doubt are provided at MRE. The method of implementation of revocation and replacement is based on the "same type" characteristics of the same owner, the same holding, the same category, the same realterms, and the same development zone. This study found that the failure of the replacement was due to law enforcement, the absence of replacement land, and human capital. The main impact is the socio-economic imbalance of the Malay community. Finally, the MRL transformation framework is developed to protect and improve the MRL that includes special committees, blueprints, agency empowerment, legal system reform, encouragement, zoning, joint venture, developing the economic power of the Malays, the addition of MRL, new normal land acquisition, awareness and education as well as the audit of MRL. The implications of this study will provide a good foundation in building new strategies to ensure that MRL is maintained as well as enhancing understanding of MRE legislation that is seen to be diminished.